2017
DOI: 10.1038/s41598-017-03918-z
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide susceptibility of Anopheles mosquitoes changes in response to variations in the larval environment

Abstract: Insecticide resistance threatens the success achieved through vector control in reducing the burden of malaria. An understanding of insecticide resistance mechanisms would help to develop novel tools and strategies to restore the efficacy of insecticides. Although we have substantially improved our understanding of the genetic basis of insecticide resistance over the last decade, we still know little of how environmental variations influence the mosquito phenotype. Here, we measured how variations in larval re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 51 publications
(59 reference statements)
0
57
0
Order By: Relevance
“…Vector control interventions need to consider variation in life history traits [7], behaviors [5], and habitats [21]. At a high nutrition diet, low temperature treatment Anopheles were found to be larger and more likely to survive exposure to a LC 50 dose of permethrin [60]. Data from our study suggest that larger doses of permethrin would be required in southern compared to northern populations of Ny.…”
Section: Discussionmentioning
confidence: 68%
“…Vector control interventions need to consider variation in life history traits [7], behaviors [5], and habitats [21]. At a high nutrition diet, low temperature treatment Anopheles were found to be larger and more likely to survive exposure to a LC 50 dose of permethrin [60]. Data from our study suggest that larger doses of permethrin would be required in southern compared to northern populations of Ny.…”
Section: Discussionmentioning
confidence: 68%
“…Aedes aegypti was unusual in their ability to survive and developed in waters ranging from pH•4 to 11. Also mosquitoes bred under different conditions showed considerable changes in mortality rates and body weight, with nutrition being the major factor, they also demonstrated that temperature, crowding and availability of nutrition during the larval stages directly or indirectly modulate 24 hours mortality in the adult when exposed to permethrin [26].…”
Section: Discussionmentioning
confidence: 95%
“…Susceptibility test data are noisy ( 29 , 30 ) and the low data volumes typically seen in resistance monitoring ( Fig. 1 ) are particularly susceptible to issues of data noise.…”
Section: Discussionmentioning
confidence: 99%